Case reportVaginal cuff dehiscence after vaginal cuff brachytherapy for uterine cancer. A case report - Cattaneo, Richard; Bellon, Maria; Elshaikh, Mohamed A. (Journal of Contemporary Brachytherapy, 2013)
Vaginal cuff dehiscence is a rare, but potentially serious complication after total hysterectomy. We report a case of vaginal cuff dehiscence after vaginal cuff brachytherapy. A 62 year old female underwent a robotic-assisted laparoscopic hysterectomy with bilateral salpingo-oophorectomy, and was found to have International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB endometrioid adenocarcinoma of the uterus. The patient was referred for adjuvant vaginal cuff brachytherapy. During the radiation treatment simulation, a computerized tomography (CT) of the pelvis showed abnormal position of the vaginal cylinder. She was found to have vaginal cuff dehiscence that required immediate surgical repair. Vaginal cuff dehiscence triggered by vaginal cuff brachytherapy is very rare with only one case report in the literature.